Eremella ryabinini (Acari, Oribatida, Eremellidae), a new oribatid mite species phoretic on Amphotis marginata (Coleoptera, Nitidulidae) from Russia - Sergey G. Ermilov; Vladimir V. Abramov (Persian Journal of Acarology)
The oribatid mite family Eremellidae (Oribatida) is recorded in the Russian fauna for the first time. A new species of the genus Eremella—E. (Eremella) ryabinini sp. nov. is described, based on phoretic adult females collected from elytron of the beetle Amphotis marginata (Fabricius) (Nitidulidae).